2007
DOI: 10.1002/ejoc.200700366
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Nucleophilic Substitution (SNOx) of the Benzylic Position as a Tunable Synthesis of Tetrahydroisoquinoline Natural Alkaloid Analogues

Abstract: Synthetic investigations of 1,3‐dichloro‐5,6‐dicyanobenzoquinone‐mediated benzylic oxidation is reported for the synthesis of natural alkaloid analogues. Extensive explorations of the oxidative nucleophilic substitution of the benzylic position of β‐phenylethylamine derivatives and the synthesis of functionalized tetrahydroisoquinolines of ecteinascidin 743 precursors have been carried out. Starting from L‐DOPA, a tunable oxazolidinone group was installed under oxidative benzylic conditions. This derivative 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 93 publications
1
15
0
Order By: Relevance
“…L-DOPA 1 is converted to corresponding methyl ester treated with thionyl chloride in methanol at room temperature [18]. L-DOPA-OMe hydrochloride 2 was *Address correspondence to this author at the Division of Applied Science, Graduate School of Agriculture, Hokkaido University; Kita 9, Nishi 9, Kitaku, Sapporo 060-8589, Japan; Tel/Fax: +81-11-7063849; E-mails: hasimoto@abs.agr.hokudai.ac.jp condensed with Boc-Gly 3 in the presence of DCC in acetonitrile and DMF at 0 °C.…”
Section: Resultsmentioning
confidence: 99%
“…L-DOPA 1 is converted to corresponding methyl ester treated with thionyl chloride in methanol at room temperature [18]. L-DOPA-OMe hydrochloride 2 was *Address correspondence to this author at the Division of Applied Science, Graduate School of Agriculture, Hokkaido University; Kita 9, Nishi 9, Kitaku, Sapporo 060-8589, Japan; Tel/Fax: +81-11-7063849; E-mails: hasimoto@abs.agr.hokudai.ac.jp condensed with Boc-Gly 3 in the presence of DCC in acetonitrile and DMF at 0 °C.…”
Section: Resultsmentioning
confidence: 99%
“…In the cited study, it was also reported that the coupling of carboxylic acids 289 with 3-phenyl-2-propen-1-yl acetate ( 288 ) in the presence of DDQ gives allyl esters 290 . DDQ was used also for the acyloxylation at the benzylic position of dimethoxyarene 291 with carboxylic acids 292 to prepare esters 293 ( Scheme 64 ) [ 243 ].…”
Section: Reviewmentioning
confidence: 99%
“…[4] We then pursued the development of a novel route for the efficient synthesis of highly functionalized 1,2,3,4-tetrahydroisoquinolines (THIQs), [5] a privileged structural motif that is frequently found in bioactive natural products and therapeutic agents. [6] In particular, C-4-oxidized THIQs [7] ex-hibit a wide range of biological activities. For example, 2azapodophyllotoxin (1), a nitrogen variant of podophyllotoxin, is a potent antitumor agent, [8] whereas 11-hydroxyerythratidine (2) exhibits curare-like, sedative, hypotensive, and central nerve system (CNS) depressant activities.…”
Section: Introductionmentioning
confidence: 99%
“…[12] However, a flexible and efficient synthetic route for all possible stereoisomers of C-1, C-3, and C-4 substituted THIQs has not yet been developed. [7,13] Most of the known asymmetric synthetic routes involve the Pictet-Spengler reaction or the Bis-Abstract: We herein report a robust and efficient synthetic route to highly functionalized enantiopure 1,2,3,4-tetrahydroisoquinolines (THIQs) from Garner aldehyde. We utilized the inherent chirality of Garner aldehyde through 1,2-and 1,3-/1,4-asymmetric inductions iteratively to obtain 1,2,3,4tetrasubstitued THIQs using rigid and isolable bridged oxazolidines without any external chiral sources.…”
Section: Introductionmentioning
confidence: 99%